Algunas calas en el tratamiento del modelo trágico por el joven Calderón - Fausta Antonucci (Mélanges de la Casa de Velázquez, 2012)
This article explores some aspects of Calderón’s tragic plays of the decade 1623-1633 from a diachronic and inter-textual viewpoint The works considered include Judas Macabeo, La gran Cenobia, La devoción de la cruz and La vida es sueño. A comparative analysis of these plays shows that the young Calderón progressively experimented with different forms of tragedy; an early stage during which he eschewed the type of tragic drama practised by his contemporary Lope and revived elements typical of Renaissance tragedy was followed by a stage of greater maturity in which he assimilated and re-worked the kinds of intrigue formerly used by Lope, of which La vida es sueño is one of the most accomplished. A comparison with Lope’s subtexts shows, among other things, how originally Calderón assimilated and handled the Aristotelian paradigm of tragedy.